Delivery from the sky : investigating visual cues to communicate robot intentions in simulated public spaces - Lingam, S.N.; Petermeijer, S.M.; Obaid, M.; Martens, M.H. (Nature, 2026)
As robots such as drones begin delivering packages from the sky in public spaces, humans will interact as recipients. Clear communication of a drone’s vertical motion and delivery intentions is essential to reduce feelings of uncertainty and build trust among the public. This study investigates how visual cues, including delivery methods and interfaces, communicate a drone’s drop-off and take-off intentions and affect recipients’ uncertainty in a simulated public environment. Through a video-based online questionnaire, 150 participants viewed scenarios where a drone delivered a package either by landing or via a cable-drop mechanism, each presented with or without visual interfaces such as onboard lights, a display, or ground projection. Participants rated the scenarios for uncertainty, understandability, predictability, trust, and convincingness, and provided qualitative feedback. Results show that visual interfaces improved participants’ ability to predict drone actions, increased certainty in approaching the drop-off spot, and improved trust. While lights posed challenges with visual clarity, both display and projection interfaces conveyed vertical motion and delivery intentions effectively. Projection was particularly recommended, as it marked the drop-off spot on the ground and a safety boundary. We discuss the implications of our findings beyond delivery scenarios, considering broader public space interactions with robots operating in vertical planes, and highlight the need for validation through real-world experiments.